Systematic desensitization to the phobia to elevators - Obregón López, Giuliana Margarita (2021)
The case study addresses a 19-year-old male patient who, in the last six months, has experienced intense and irrational fear of entering elevators in the various contexts. As a consequence, the patient has progressively isolated himself from his friends at university, friends from work, from his relatives and from his girlfriend, in order to avoid using the elevators and hide the phobia. The systematic desensitization technique is used in the treatment. This procedure allows the patient to learn to be exposed to the stimuli that generate aversion and in this case it is to use the elevator. The systematic desensitization technique includes the process of training in progressive muscle relaxation, establishing a hierarchy with situations that generate anxiety, training in the imagination through a gradual exposure of anxiety situations and live exposure to unpleasant situations. The intervention process takes place in ten sessions. This is an applied research and uses a univariate multiconditional design of Applied Behavior Analysis (ABA). The results indicate that, in the pretreatment baseline,fourteen problem behaviors were identified; in comparison to the measurement of the post-treatment line, where the problem behaviors were not identified. Therapeutic benefits were maintained after one month of follow-up.